BIOTEKNOLOGI UNTUK PERTANIAN NEGARA BERKEMBANG: MANFAAT, RESIKO, DAN KEBIJAKAN - Sutawi, Sutawi (Jurnal Bestari, 2001)
Increasing food surviving both quality and quantity and genetic engineering by transgenic biotechnology is an appropriate choice must grow in the developing countries. Nevertheless transgenic biotechnology has not only benefit but also risk, both technological and sociological ones. Eliminating these risks, it is necessary to think the strategic policy with the solution for the poor.